The first Lithuanian Archaeological expedition in Afghanistan - Aleksiejus Luchtanas; Ramunė Butrimaitė (Lietuvos Istorijos Studijos)
Afghanistan is most considerable for its historical, political, and geographical situation, however this region of Central Asia is least explored. The country falls into the sphere of East Iran and Indo valley cultures influence. Afghanistan carries its rich history, which reflects in most monuments of culture. The earliest records of Afghanistan's cultural heritage are the accounts of travelers, first Chinese, then Muslim, and finally European. Interest in Afghanistan's cultural heritage grew in the 20th century with the archaeological expeditions provided by Italian, Indian, German, Japanese, Russian, French, and American scientists. The end of the 20th century was marked by the regression of activities in the cultural sphere. Only after 2001 did the works of heritage reestablishment begin. The priority of the Afghanistan government and UNESCO is the search, documentation, and registering of cultural heritage sites.